PENGARUH ORANG TUA TERHADAP PRESTASI SISWA DI SMK AL-INSAN KEROTEK CILEGON - Bangun Yoga Wibowo; Meilla Dwi Nurmala (Jurnal Penelitian Bimbingan dan Konseling, 2024)
The research aims to determine whether the influence of parents on student achievement at Al-Insan Kerotek Cilegon Vocational School is interrelated through the independent variable (X) and the dependent variable (Y). This research uses a quantitative approach with descriptive research correlation methods.The data in this research came from teachers and students of XI IPA SMK Al-Insan Kerotek Cilegon.Data collection was obtained based on the results of observing and analyzing the influence of parents on student achievement and providing questionnaires from 30 samples with a total of 110 class XI Science students.The research results state that the role of parents is very important in student achievement by providing motivation and support to students. The role of parents is a dual role that has a significant relationship. The results of the questionnaire calculations were 33.5%, while the remaining 66.5% was influenced by other factors.Keywords: Parent, Student, Performance